2D Nanomaterial Supported Single‐Metal Atoms for Heterogeneous Photo/Electrocatalysis - Yan, Cheng; Liu, Yi‐Lin; Zeng, Qingyi; Wang, Gui‐Gen; Han, Jie‐Cai (Advanced functional materials, 2023)
Single‐atom catalysts (SACs) attract intensive attention owing to their unmatched catalytic activities and high atom utilization. Besides metal species themselves, the substrates play a key role for the improvement of their catalytic performance by optimizing metal–support interactions and coordination structures. In the past years, various 2D nanomaterials have been employed to anchor single metal atoms for renewable energy technologies and other important industrial processes. Tremendous progress has been achieved in the development of 2D supported SACs for advanced energy conversion reactions. This article provides a comprehensive and critical review of up‐to‐date advances in the field of 2D supported SACs. The state‐of‐the‐art characterizations including ex/in situ microscopic and spectroscopic techniques are summarized with the emphasis on their specific superiorities in identifying the reactive sites and reaction mechanisms, combined with theoretical calculations and experimental results. A brief overview of various reactions including hydrogen evolution reaction (HER), oxygen evolution reaction (OER), two‐electron oxygen reduction reaction (2e‐ORR), carbon dioxide reduction (CO2RR), and nitrogen reduction reaction (NRR) under the framework of electrocatalysis and photocatalysis, is presented on basis of versatile 2D nanomaterial supports. Last, the key challenges and opportunities in this rising field are highlighted. This review article presents advances in 2D nanomaterial supported single metal atom catalysts (SACs) toward photo/electrocatalysis, with the special emphasis on the superiorities of 2D nanosheets as host materials. Advanced ex/in situ microscopic and spectroscopic approaches as well as rational design strategies of 2D‐SACs, are comprehensively summarized. The future challenges and opportunities on the 2D nanosheets‐supported SACs for photo/electrocatalysis are highlighted.